Analisa Luasan Terumbu Karang Berdasarkan Pengolahan Data Citra Satelit Lansat 8 menggunakan Algoritma Lyzenga - Laila Martina Azka (Politeknik Negeri Malang, 2019)
Indonesia has the potential of invaluable biological resources from an economic and ecological perspective, one of which is coral reef resources. To determine the condition of the coral reef ecosystem in Indonesian waters as an effort to monitor and monitor using remote sensing data. The purpose of this research is the creation of an information system through a website that can help users access information effectively and efficiently.Utilization of Landsat 8 satellite image data to observe the bottom of the waters directly on coral reef mapping using the Lyzenga Algorithm method, also known as the depthinvariant index method or the water column correction method. This method produces a baseline index that is not affected by depth and works well in clear shallow waters such as in coral reef habitat areas (Maritorena, 1996). The results showed that the image processing data had a map accuracy level for Menjangan Besar and Menjangan Kecil islands of 77.78%, while the map accuracy level for Karimunjawa and Kemujang Islands was 72.23%. And from the processed data, it is known that coral reef cover in general has increased from 2014 to 2018, for Karimunjawa and Kemujan Islands an increase of 17.4% for Menjangan Besar and Menjangan Kecil Islands only a slight increase of 0.27% and for Bunaken Island an increase of 9.1%. And there is one island that is processed has decreased, namely Bunaken Island by 4.5%.